1994
DOI: 10.1111/j.1365-2338.1994.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Une souche nécrogène du plum pox potyvirus provoque un dépérissement sur certains cultivars de pêcher1

Abstract: Une souche du plum pox potyvirus, PPV. SP, collectée dans un verger de pêcher du sud‐est de la France, a été sélectionnée après transmission par Myzus persicae et maintenue sur Prunus persica GF305. L'étude de la vitesse de migration de la sous‐unité de la protéine capside en électro‐immunoblot, critère de différenciation efficace des souches et isolats de PPV, a permis de classer cette souche dans le sérogroupe M de Kerlan & Dunez. Ce résultat a été confirmé par PCR sur la base d'un polymorphisme de restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Conducted molecular analyses showed PPV-Rec (65%) and PPV-D (2.5%) as the most and less dominant strains in the orchard, respectively and confirmed our previous study for strain composition of PPV in the region of Troyan (not published), where PPV-Rec (71.2%) was found as The twofold serological assays performed each year indicate a relatively low speed (11.2%) of PPV spread, which is similar to the reported 9.25% rate of infection in 4 years in an experimental plum orchard in Serbia (Jevremović, 2012). The observed in peach orchard blocks annual disease incidence between 2% and 6% (Dallot, Gottwald, Labonne, & Quiot, 2003), is in contrast to the much greater spread of PPV-D and PPV-M strains recorded by Llacer, Avinent, and Hermoso de Mendoza (1992), Adamolle, Boeglin, Labonne, Candresse, and Quiot (1994), Cambra et al (2004) and Varveri (2006). Both biotic (virus characteristics, transmission efficiency, dynamics of vector populations, susceptibility of host plant) and abiotic (climate, landscape characteristics) factors impact sharka disease prevalence and spread (Rimbaud et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Conducted molecular analyses showed PPV-Rec (65%) and PPV-D (2.5%) as the most and less dominant strains in the orchard, respectively and confirmed our previous study for strain composition of PPV in the region of Troyan (not published), where PPV-Rec (71.2%) was found as The twofold serological assays performed each year indicate a relatively low speed (11.2%) of PPV spread, which is similar to the reported 9.25% rate of infection in 4 years in an experimental plum orchard in Serbia (Jevremović, 2012). The observed in peach orchard blocks annual disease incidence between 2% and 6% (Dallot, Gottwald, Labonne, & Quiot, 2003), is in contrast to the much greater spread of PPV-D and PPV-M strains recorded by Llacer, Avinent, and Hermoso de Mendoza (1992), Adamolle, Boeglin, Labonne, Candresse, and Quiot (1994), Cambra et al (2004) and Varveri (2006). Both biotic (virus characteristics, transmission efficiency, dynamics of vector populations, susceptibility of host plant) and abiotic (climate, landscape characteristics) factors impact sharka disease prevalence and spread (Rimbaud et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…The twofold serological assays performed each year indicate a relatively low speed (11.2%) of PPV spread, which is similar to the reported 9.25% rate of infection in 4 years in an experimental plum orchard in Serbia (Jevremović, ). The observed in peach orchard blocks annual disease incidence between 2% and 6% (Dallot, Gottwald, Labonne, & Quiot, ), is in contrast to the much greater spread of PPV‐D and PPV‐M strains recorded by Llacer, Avinent, and Hermoso de Mendoza (), Adamolle, Boeglin, Labonne, Candresse, and Quiot (), Cambra et al. () and Varveri ().…”
Section: Discussionmentioning
confidence: 93%
“…The speed at which the virus spread in this study was less than in cases in Spain (Llacer et al, 1992), where it required between 2 and 5 yr to reach 100%. A study in France described periods of 8 to 9 yr to reach 100% infection (Adamolle et al, 1994). The results of this work suggest that all the factors for virus spreading in field are present.…”
Section: Epidemiologymentioning
confidence: 71%
“…Studies on virus spread in apricot orchards have been reported in Spain and France where D‐type isolates are prevalent. In Spain total infection occurred within 2–5 years (Llacer et al., 1992), whereas in France this occurred after 8–9 years (Adamolle et al., 1994). Gottwald et al.…”
Section: Resultsmentioning
confidence: 99%